Analisis Kebutuhan Bahan Perkerasan Lentur Pada Proyek Rekonstruksi Jalan Batas Barru - Takkalalla Kabupaten Soppeng - Jihan Putri Rahmadani; Abdul Rahim Nurdin; Tamrin Mallawangeng (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Pavement is an important element in road construction consisting of a layer of aggregate and binder, which serves to support traffic loads and protect the soil layer from climate change and great pressure. Based on the type of binder, pavements are divided into flexible, rigid and composite pavements. This research provides an overview of the planning and quality testing of flexible pavement, and aims to analyze the volume requirements and thickness of flexible pavement in road projects using secondary data from PT Mareraya Multipratama Jaya and Bina Marga 2018 (Revision 2) specifications. The main focus is on flexible pavement that uses asphalt as the main binder, with a 6 cm thick LASTON AC-BC layer and 4 cm thick LASTON AC-WC. The method used is observation through secondary data collection, including analysis of pavement thickness as well as the volume of the mixture of aggregates, asphalt, and fillers. The analysis showed that the total volume of AC-BC and AC-WC mixes were 3302.35 tons and 2104.09 tons, respectively, with bitumen volume of 183.28 tons for AC-BC and 127.93 tons for AC-WC. There was a significant difference in core drill thickness between the self-inspection and inspectorate inspection, the inspectorate inspection showed lower density. Factors such as traffic load, asphalt aging, and environmental conditions may influence the difference in results.